A new empirical propagation model depending on volumetric density in citrus orchards for wireless sensor network applications at sub‐6 GHz frequency region. Issue 9 (7th June 2021) - Dogan, Habib
Abstract: The accuracy of the path loss models directly affects the performance of the wireless sensor networks (WSN) and the efficiency of coverage planning. In this article, as a novelty, new empirical path loss models with foliage depth are proposed at two different 5G frequencies (3.5 and 4.2 GHz) based on volumetric density rate ( v ) of the trees in citrus orchards for WSN. In order to generate/verify empirical models, measurements are performed at different locations with similar environment characteristics. First, the measurements are compared with commonly used empirical models such as LITU‐R, FITU‐R, Cost 235, and log‐normal, and they are found to be compatible with these models. Second, empirical path loss model is generated based on these measurements. Accordingly, for 3.5 and 4.2 GHz, the coefficient of determination ( R 2 ) values are 0.966 and 0.965, respectively. Thirdly, based on the proposed model, it is determined that increasing the v value by 30% increased path loss by 20 dB. Finally, the performance of the proposed models is compared with four different empiric models for calculated v as 0.571. Additionally, the 3.08 and 3.46 root mean square error values of the proposed models are considerably better than those of other models.